Vinyl modified polyphenyl ether / polystyrene alloy resin as well as composite material and preparation method thereof
Through the preparation method of vinyl modified polyphenylene ether/polystyrene alloy resin, the compatibility and interface bonding force of the polymer are improved by acrylic monomers and silane coupling agents, and the problem of poor interfacial compatibility of polyphenylene ether/polystyrene alloy in composite sheets is solved, which significantly improves the toughness and comprehensive performance of the composite material.
Patent Information
- Application Number
- CN202411978338.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-25
AI Technical Summary
Polyphenylene ether/polystyrene alloys have problems such as poor interfacial compatibility and different shrinkage rates in fiber-reinforced composite sheets, resulting in large internal stress, poor comprehensive performance, especially poor toughness and easy cracking.
Through the preparation method of vinyl modified polyphenylene ether/polystyrene alloy resin, an acrylic monomer is used to conduct an esterification reaction with polyphenylene ether to increase the vinyl functionality of the polyphenylene ether, improve its compatibility with polystyrene, and enhance the interface binding force through a silane coupling agent to form a covalent bond to connect the polymer matrix and glass fiber.
The interface compatibility and bonding force of polyphenylene ether/polystyrene alloy resin is improved, the internal stress is reduced, and the toughness and comprehensive performance of the composite material are significantly improved.
Smart Images

Figure BDA0005220944710000061 
Figure BDA0005220944710000062
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a vinyl-modified polyphenylene ether / polystyrene alloy resin and a composite material thereof and a preparation method thereof. Background Art
[0002] Polyphenylene ether is a high-performance engineering plastic with a high glass transition temperature and heat resistance, mechanical strength and flame retardancy, but relatively weak polarity. Polystyrene is a general-purpose plastic with good processing performance and toughness, but relatively low heat resistance, and the processing temperature difference between the two is large. This difference in chemical structure and processing temperature leads to poor compatibility between the two in the alloy, which is prone to phase separation and affects the interface bonding. At the same time, due to the different surface energies of polyphenylene ether and polystyrene, there is a large interfacial tension between the two. This interfacial tension will hinder the diffusion and mutual penetration of molecules, thereby affecting the interface bonding. The interfacial tension will also lead to the formation of interface defects in the alloy, such as voids, cracks, large internal stress, etc., which will reduce the mechanical properties and durability of the alloy.
[0003] The surface of glass fiber is smooth and chemically inert, and its bonding with polyphenylene ether / polystyrene alloy mainly relies on physical adsorption and mechanical intercalation. This bonding method is relatively weak and is prone to interfacial debonding under stress or environmental factors. In addition, due to the high processing temperature and poor fluidity of conventional polyphenylene ether / polystyrene alloys, it is difficult to effectively infiltrate glass fiber fabrics when preparing thermoplastic glass fiber composites. At present, commonly used interface treatment methods include coupling agent treatment and plasma treatment. Coupling agent treatment is affected by the type, dosage and treatment process of the coupling agent, and it is difficult to achieve the best interface bonding effect; plasma treatment is costly, and the stability of the treatment effect needs to be improved. At the same time, improper interface treatment may have a negative impact on the performance of the composite material. For example, excessive coupling agent treatment may cause the toughness of the composite material to decrease, and plasma treatment may cause material degradation or discoloration. Summary of the invention
[0004] The main purpose of the present invention is to provide a vinyl modified polyphenylene ether / polystyrene alloy resin to solve the problems of poor interface compatibility, large internal stress caused by different shrinkage rates, poor comprehensive performance, especially poor toughness and easy cracking in polyphenylene ether / polystyrene and its fiber reinforced composite plate in the prior art.
[0005] Another object of the present invention is to provide a method for preparing the vinyl modified polyphenylene ether / polystyrene alloy resin, which has a simple process and is suitable for large-scale production.
[0006] Another object of the present invention is to provide a high-strength and high-toughness glass fiber reinforced composite material, which comprises the vinyl-modified polyphenylene ether / polystyrene alloy resin and has high strength and high toughness properties.
[0007] Another object of the present invention is to provide a method for preparing the high-strength and high-toughness glass fiber reinforced composite material, which is prepared by high-temperature hot pressing and is easy to industrialize.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] The first aspect of the present invention provides a vinyl modified polyphenylene ether / polystyrene alloy resin, which includes the following raw materials in parts by weight: 30 to 70 parts by weight of polyphenylene ether, 30 to 70 parts by weight of styrene, 1 to 3 parts by weight of acrylic monomer, 0.5 to 1 part by weight of catalyst, 0.5 to 2 parts by weight of initiator, 1 to 3 parts by weight of silane coupling agent, 3 to 16 parts by weight of flame retardant, 0.2 to 0.6 parts by weight of antioxidant, 0.3 to 1 part by weight of heat stabilizer, 0.2 to 0.4 parts by weight of light stabilizer, and 0.05 to 0.1 parts by weight of ultraviolet light absorber.
[0010] Preferably, the vinyl-modified polyphenylene ether / polystyrene alloy resin is a powdered resin.
[0011] Preferably, the hydroxyl value of the polyphenylene ether is 50 to 1000 g / mol, more preferably 850 g / mol.
[0012] Preferably, the raw materials of the vinyl-modified polyphenylene ether / polystyrene alloy resin include, by weight: 70 parts by weight of polyphenylene ether, 30 parts by weight of styrene, 3 parts by weight of acrylic monomer, 1 part by weight of catalyst, 2 parts by weight of initiator, 3 parts by weight of silane coupling agent, 7 parts by weight of flame retardant, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light absorber.
[0013] Preferably, the acrylic monomer is acrylic acid or methacrylic acid;
[0014] and / or the catalyst is p-toluenesulfonic acid;
[0015] and / or the initiator is benzoyl peroxide;
[0016] and / or the silane coupling agent is γ-methacryloxypropyltrimethoxysilane;
[0017] and / or the flame retardant is selected from one or more of tetraphenyl (bisphenol-A) diphosphate, tetraphenyl resorcinol diphosphate, aluminum hypophosphite, sodium hypophosphite, and melamine cyanurate;
[0018] and / or the antioxidant is one or more of tris(nonylphenyl)phosphite, distearylthiopropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl alcohol ester, and 2,2-methylenebis(4-methyl-6-tert-butylphenol);
[0019] and / or the heat stabilizer is one or more of triphenyl phosphite, tris(2,6-dimethylphenyl) phosphite, and trimethyl phosphate;
[0020] and / or the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole;
[0021] And / or the ultraviolet light absorber is one or more of titanium oxide, cerium oxide and zinc oxide.
[0022] The second aspect of the present invention provides a method for preparing the vinyl-modified polyphenylene ether / polystyrene alloy resin, comprising the following steps:
[0023] (1) dissolving polyphenylene ether and acrylic monomer in a solvent and mixing them evenly, passing nitrogen gas for protection, slowly dropping a catalyst, heating and stirring in an oil bath to carry out an esterification reaction, the reaction temperature is 60 to 120° C., the reaction time is 2 to 10 hours, and after the reaction is completed, cooling, filtering, and removing the solvent to obtain a vinyl-modified polyphenylene ether;
[0024] (2) The vinyl-modified polyphenylene ether obtained in step (1) is mixed evenly with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer, and an ultraviolet light absorber in a mixing device to obtain a premixed material, and a free radical in-situ polymerization reaction is carried out in a flat vulcanizer at a reaction temperature of 130 to 160° C. for a reaction time of 1 to 5 h. After the reaction is completed, the premixed material is cooled to room temperature, vacuum dried, and crushed to obtain the premixed material.
[0025] During the preparation of the above-mentioned vinyl-modified polyphenylene ether / polystyrene alloy resin, the carboxyl group of the acrylic monomer undergoes an esterification reaction with the terminal hydroxyl group of the molecular chain of the polyphenylene ether to obtain a vinyl-modified polyphenylene ether, which can realize the vinyl functionalization of the polyphenylene ether, not only increasing the compatibility of the polyphenylene ether in the styrene monomer, but also enabling it to participate in the polymerization reaction of styrene as a macromolecular monomer.
[0026] The third aspect of the present invention provides a high-strength and high-tenacity glass fiber reinforced composite material, which includes the following raw materials in parts by weight: 30 to 70 parts by weight of glass fiber cloth, 30 to 70 parts by weight of vinyl modified polyphenylene ether, 30 to 70 parts by weight of styrene, 0.5 to 2 parts by weight of initiator, 1 to 3 parts by weight of silane coupling agent, 3 to 16 parts by weight of flame retardant, 0.2 to 0.6 parts by weight of antioxidant, 0.3 to 1 parts by weight of heat stabilizer, 0.2 to 0.4 parts by weight of light stabilizer, and 0.05 to 0.1 parts by weight of ultraviolet light absorber.
[0027] Preferably, the high-strength and high-tenacity glass fiber reinforced composite material includes the following raw materials in parts by weight: 55 parts by weight of glass fiber cloth, 37 parts by weight of vinyl modified polyphenylene ether, 16 parts by weight of styrene, 2 parts by weight of initiator, 3 parts by weight of silane coupling agent, 7 parts by weight of flame retardant, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light absorber.
[0028] Preferably, the density of the glass fiber cloth is 500-600 g / m 2 .
[0029] Preferably, the flame retardant is selected from one or more of tetraphenyl (bisphenol-A) diphosphate, tetraphenyl resorcinol diphosphate, aluminum hypophosphite, sodium hypophosphite, and melamine cyanurate;
[0030] and / or the antioxidant is one or more of tris(nonylphenyl)phosphite, distearylthiopropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl alcohol ester, and 2,2-methylenebis(4-methyl-6-tert-butylphenol);
[0031] and / or the heat stabilizer is one or more of triphenyl phosphite, tris(2,6-dimethylphenyl) phosphite, and trimethyl phosphate;
[0032] and / or the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole;
[0033] And / or the ultraviolet light absorber is one or more of titanium oxide, cerium oxide and zinc oxide.
[0034] Preferably, the high-strength and high-tenacity fiber-reinforced composite plate has a thickness of 1.0 to 5.0 mm.
[0035] A fourth aspect of the present invention provides a method for preparing the high-strength and high-tenacity glass fiber reinforced composite material, comprising the following steps:
[0036] (i) the vinyl-modified polyphenylene ether is uniformly mixed with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer and an ultraviolet light absorber in a mixing device according to a certain proportion to obtain a premixed material;
[0037] (ii) applying a release agent on the mold, alternately stacking the glass fiber cloth and the premix, hot pressing at 180-220° C. for 20-40 min under a pressure of 20 MPa, cooling and demoulding, and performing post-treatment to obtain a high-strength and high-toughness glass fiber reinforced composite material.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. Acrylic monomers are grafted onto polyphenylene ether to obtain vinyl-modified polyphenylene ether, which provides some unsaturated double bonds for polyphenylene ether and realizes the vinyl functionalization of polyphenylene ether. It can participate in the polymerization reaction of styrene as a macromolecular monomer, and the interfacial compatibility between it and polystyrene is increased. The melt blending of the two can reduce the phase separation phenomenon.
[0040] 2. After the vinyl modified polyphenylene ether is uniformly dissolved with styrene, silane coupling agent, etc., a free radical in-situ polymerization reaction is carried out to obtain a vinyl modified polyphenylene ether / polystyrene alloy resin, wherein the methacryloyloxy group at one end of the silane coupling agent chemically reacts with the vinyl modified polyphenylene ether and styrene to form a chemical bond connection, thereby enhancing the compatibility and bonding force between the polymer matrices and making the performance more stable; the methoxysilane group at the other end of the silane coupling agent reacts with the silanol group on the surface of the glass fiber to form a covalent bond, which can enhance the interfacial bonding force of the organic / inorganic two phases. The three-phase materials of polyphenylene ether, polystyrene and glass fiber cloth, which were originally only combined by intermolecular forces, are effectively linked together by covalent bonds, thereby reducing the internal stress generated at the interface due to the different shrinkage rates of the three-phase materials during the material molding process, forming a strong interface bond between the glass fiber and the polymer matrix, and greatly improving the comprehensive performance of the composite board.
[0041] 3. Silane coupling agent can improve the uniform dispersion of vinyl modified polyphenylene ether and polystyrene in the polymer and reduce the phase separation phenomenon. It can also be used as a lubricant to improve the dispersion of glass fiber in the polymer matrix, improve weather resistance and chemical corrosion resistance, and adjust processing performance, reduce viscosity, and improve demolding properties, playing a key role in improving the comprehensive performance of fiberboard.
[0042] 4. In the present invention, glass fiber cloth and premix of vinyl modified polyphenylene ether and styrene are alternately stacked and then hot-pressed to obtain a high-strength and high-tenacity fiber-reinforced composite plate with good interface compatibility and a simple preparation process. The problems of high processing temperature, poor fluidity, difficulty in wetting continuous fiber fabrics, and poor compatibility with polystyrene alloys and its fiber interface in the prior art of polyphenylene ether are effectively solved, and the plate has good application prospects. DETAILED DESCRIPTION
[0043] In order to more fully understand and demonstrate the technical solutions, purposes and advantages of the present invention, the technical effects produced by the present invention are further described in detail and completely in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all. It should be pointed out that for those of ordinary skill in the art, other embodiments obtained without departing from the concept of the present invention all belong to the protection scope of the present invention.
[0044] The raw materials used are as follows:
[0045] Polyphenylene ether: analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.
[0046] Acrylic acid: analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0047] Benzoyl peroxide (BPO): analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0048] p-Toluenesulfonic acid: analytical grade, produced by Beijing Yancheng Technology Co., Ltd.;
[0049] Styrene: analytical grade, produced by Beijing Yancheng Technology Co., Ltd.;
[0050] γ-Methacryloxypropyltrimethoxysilane (KH-570): analytical grade, produced by Beijing Yancheng Technology Co., Ltd.;
[0051] Aluminum hypophosphite: analytical grade, produced by Beijing Huawei Ruike Chemical Co., Ltd.;
[0052] Triphenyl phosphite: analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0053] 2-(2-Hydroxy-5-methylphenyl)benzotriazole: analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0054] Zinc oxide: analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0055] Titanium oxide: analytical grade, produced by Shanghai MacLean Biochemical Technology Co., Ltd.;
[0056] Cerium oxide: analytical grade, produced by Shanghai MacLean Biochemical Technology Co., Ltd.;
[0057] Aluminum chloride: analytical grade, produced by Beijing Huawei Ruike Chemical Co., Ltd.;
[0058] Tetraphenyl (bisphenol-A) diphosphate: analytical grade, produced by Beijing Huawei Ruike Chemical Co., Ltd.;
[0059] 3,5-di-tert-butyl-hydroxyphenylpropionic acid octadecyl ester: analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0060] 2,2-Methylenebis(4-methyl-6-tert-butylphenol): analytical grade, produced by Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0061] Tris(nonylphenyl) phosphite: analytical grade, produced by Shanghai MacLean Biochemical Technology Co., Ltd.;
[0062] Distearyl thiopropionate: analytical grade, produced by Shanghai MacLean Biochemical Technology Co., Ltd.;
[0063] Octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate: analytical grade, produced by Shanghai MacLean Biochemical Technology Co., Ltd.
[0064] Example 1
[0065] In this embodiment, a high-strength and high-tenacity fiber-reinforced composite plate is prepared by synthesizing the following raw materials in parts by weight:
[0066] The vinyl-modified polyphenylene ether resin is produced from the following raw materials in parts by weight: 70 parts by weight of polyphenylene ether, 3 parts by weight of acrylic monomer, and 1 part by weight of catalyst.
[0067] The high-strength and high-tenacity fiber-reinforced composite board is produced from the following raw materials in parts by weight: 55 parts by weight of glass fiber cloth, 38 parts by weight of vinyl-modified polyphenylene ether, 17 parts by weight of styrene, 2 parts by weight of initiator, 3 parts by weight of silane coupling agent, 7 parts by weight of flame retardant, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light additive.
[0068] Among them, the acrylic monomer is acrylic acid; the catalyst is p-toluenesulfonic acid; the initiator is BPO; the silane coupling agent is KH-570; the flame retardant is aluminum hypophosphite; the antioxidant is 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl ester; the heat stabilizer is triphenyl phosphite; the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole; and the ultraviolet light absorber is zinc oxide.
[0069] The steps for preparing high-strength and high-tenacity fiber-reinforced composite panels are as follows:
[0070] (1) Polyphenylene ether and acrylic monomer are dissolved in a solvent and mixed evenly, and nitrogen is passed through the solvent. The catalyst is slowly added dropwise, and the mixture is heated and stirred in an oil bath to react. The reaction temperature is 70° C. and the reaction time is 2 h. After the reaction is completed, the mixture is cooled, filtered, and the solvent is removed to obtain vinyl-modified polyphenylene ether. The reaction formula is as follows:
[0071]
[0072] (2) The vinyl-modified polyphenylene ether obtained in step (1) is mixed evenly with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer, and an ultraviolet light absorber in a mixing device to obtain a premixed material.
[0073] (3) Apply release agent on the mold, cut the glass fiber cloth, and alternately lay the glass fiber cloth (500-600g / m 2 ) and the aforementioned premixed materials, and then heated at 200°C for 0.5h, the vulcanizing machine pressure is 20MPa, cooled, demoulded and post-treated, to obtain, the reaction formula is as follows:
[0074]
[0075] Example 2
[0076] In this embodiment, a high-strength and high-tenacity fiber-reinforced composite plate is prepared by synthesizing the following raw materials in parts by weight:
[0077] The vinyl-modified polyphenylene ether resin is produced from the following raw materials in parts by weight: 50 parts by weight of polyphenylene ether, 2.15 parts by weight of acrylic monomer, and 1 part by weight of catalyst.
[0078] The high-strength and high-tenacity fiber-reinforced composite board is produced from the following raw materials in parts by weight: 55 parts by weight of glass fiber cloth, 28 parts by weight of vinyl-modified polyphenylene ether, 28 parts by weight of styrene, 1.5 parts by weight of initiator, 3 parts by weight of silane coupling agent, 7 parts by weight of flame retardant, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light absorber.
[0079] Among them, the acrylic monomer is acrylic acid; the catalyst is p-toluenesulfonic acid; the initiator is BPO; the silane coupling agent is KH-570; the flame retardant is aluminum hypophosphite; the antioxidant is 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl ester; the heat stabilizer is triphenyl phosphite; the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole; and the ultraviolet light absorber is zinc oxide.
[0080] The steps for preparing high-strength and high-tenacity fiber-reinforced composite panels are as follows:
[0081] (1) Polyphenylene ether and acrylic monomer are dissolved in a solvent and mixed evenly, and nitrogen is passed through the solvent to slowly drop the catalyst, and the mixture is heated and stirred in an oil bath to react at a temperature of 70° C. for a reaction time of 2 h. After the reaction is completed, the mixture is cooled, filtered, and the solvent is removed to obtain vinyl-modified polyphenylene ether.
[0082] (2) The vinyl-modified polyphenylene ether obtained in step (1) is mixed evenly with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer, and an ultraviolet light absorber in a mixing device to obtain a premixed material.
[0083] (3) Apply release agent on the mold, cut the glass fiber cloth, and alternately lay the glass fiber cloth (500-600g / m 2 ) and the aforementioned premixed materials, and then heated at 200°C for 0.5h, with a vulcanizing machine pressure of 20MPa, cooled, demoulded and post-treated to obtain.
[0084] Example 3
[0085] In this embodiment, a high-strength and high-tenacity fiber-reinforced composite plate is prepared by synthesizing the following raw materials in parts by weight:
[0086] The vinyl-modified polyphenylene ether resin is produced from the following raw materials in parts by weight: 30 parts by weight of polyphenylene ether, 1.29 parts by weight of acrylic monomer, and 0.7 parts by weight of catalyst.
[0087] The high-strength and high-tenacity fiber-reinforced composite board is produced from the following raw materials in parts by weight: 55 parts by weight of glass fiber cloth, 17 parts by weight of vinyl-modified polyphenylene ether, 38 parts by weight of styrene, 1 part by weight of initiator, 3 parts by weight of silane coupling agent, 7 parts by weight of flame retardant, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light absorber.
[0088] Among them, the acrylic monomer is acrylic acid; the catalyst is p-toluenesulfonic acid; the initiator is BPO; the silane coupling agent is KH-570; the flame retardant is aluminum hypophosphite; the antioxidant is 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl ester; the heat stabilizer is triphenyl phosphite; the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole; and the ultraviolet light absorber is zinc oxide.
[0089] The steps for preparing high-strength and high-tenacity fiber-reinforced composite panels are as follows:
[0090] (1) dissolving polyphenylene ether and acrylic monomer in a solvent and mixing them evenly, and passing nitrogen gas for protection, slowly dropping a catalyst, heating and stirring in an oil bath to react, the reaction temperature is 70° C., the reaction time is 2 h, and after the reaction, cooling, filtering, removing solvent and other post-treatments are performed to obtain vinyl-modified polyphenylene ether;
[0091] (2) The vinyl-modified polyphenylene ether obtained in step (1) is mixed evenly with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer, and an ultraviolet light absorber in a mixing device to obtain a premixed material.
[0092] (3) Apply release agent on the mold, cut the glass fiber cloth, and alternately lay the glass fiber cloth (500-600g / m 2 ) and the aforementioned premixed materials, and then heated at 200°C for 0.5h, with a vulcanizing machine pressure of 20MPa, cooled, demoulded and post-treated to obtain.
[0093] Example 4
[0094] The raw materials and preparation method of this embodiment are the same as those of embodiment 1, and the only difference is that the amount of silane coupling agent is replaced by 2 parts by weight from 3 parts by weight.
[0095] Example 5
[0096] The raw materials and preparation methods of this embodiment are the same as those of embodiment 1, and the only difference is that the amount of silane coupling agent is replaced from 3 parts by weight to 1 part by weight.
[0097] Comparative Example 1
[0098] The only difference between this comparative example and Example 1 is that no silane coupling agent is added, that is, the vinyl-modified polyphenylene ether and polystyrene are directly polymerized and extruded to prepare the powdered modified material.
[0099] Comparative Example 2
[0100] Compared with Example 1, this comparative example removes the acrylic monomer and the silane coupling agent from the original formula, does not include step (1), does not perform vinyl functionalization on the polyphenylene ether, and does not add the silane coupling agent during the polymerization process. That is, the polyphenylene ether and polystyrene are directly polymerized and extruded to prepare the powder modified material.
[0101] Effect comparison ratio
[0102] In order to verify the technical effect of the high-strength and high-tenacity fiber-reinforced composite plate of the present invention, the following tests were conducted:
[0103] The high-strength and high-tenacity fiber-reinforced composite plates prepared in Comparative Examples 1-2 and Examples 1-5 were taken as samples to be tested, and tensile strength tests, interlaminar shear strength tests and impact strength tests were performed on them respectively. The specific steps are as follows:
[0104] A universal testing machine (MTS E43.104) was used to test the compressive strength of the samples according to ASTM-D638-14a. The test speed was set to 1 mm / min on the universal testing machine, and a flat plate fixing tool was selected to ensure that the sample was firmly clamped. Subsequently, a static tensile test at a low strain rate was performed and the tensile strength was recorded. Each group was measured three times and the average value was taken.
[0105] Use a universal testing machine (MTS E43.104) to test the interlaminar shear strength of the sample according to GB / T 1450.1-2005. Cut the glass fiber composite sheet into 5×5cm samples. Debug the universal material testing machine, set the loading speed to 10mm / min, install the sample in the fixture, ensure that the interlaminar shear surface is perpendicular to the loading direction, start the testing machine for testing, record the force and displacement data, and stop loading when the sample undergoes interlaminar shear failure. Read the maximum shear force value from the testing machine, calculate the interlaminar shear strength, measure three times for each group, and take the average value.
[0106] The impact strength of the samples to be tested was tested using a simply supported beam impact tester according to GT / B1451-2005. The test rate was 3.8 m / s, and each group was measured three times. The average value was taken and the results are shown in Table 1.
[0107] Table 1
[0108] Serial number Tensile strength(MPa) Interlaminar shear strength (MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 662 31.5 355 Example 2 558 28.5 317 Example 3 567 22.8 223 Example 4 605 28.7 339 Example 5 536 26.5 321 Comparative Example 1 475 23.6 226 Comparative Example 2 409 20.5 207
[0109] From the results of Comparative Example 1 and Examples 1, 4, and 5, it can be seen that the tensile strength, interlaminar shear strength, and impact strength of the vinyl-modified polyphenylene ether / polystyrene alloy fiber composite sheet without silane coupling agent are relatively low. With the increase of silane coupling agent, the tensile strength, interlaminar shear strength, and impact strength of the fiber composite sheet also increase accordingly, indicating that the presence of silane coupling agent can improve the wettability between fiber and resin, so that the polymer can better infiltrate the fiber surface and reduce the gaps and defects at the interface. In addition, the silane coupling agent can also adjust the polarity and chemical properties of the interface, making it closer to the properties of vinyl-modified polyphenylene ether / polystyrene alloy, thereby improving the interfacial compatibility. The improvement of interfacial compatibility helps to improve the overall performance of the composite sheet, including modulus and tensile strength, because the reduction of defects reduces the possibility of stress concentration, so that the material can withstand external forces more evenly. When there is no silane coupling agent, the interfacial compatibility of vinyl-modified polyphenylene ether / polystyrene alloy and fiber may be poor, resulting in defects or stress concentration points that are prone to occur at the interface.
[0110] From the results of Comparative Examples 1 and 2, it can be seen that the tensile strength, interlaminar shear strength and impact strength of the polyphenylene ether / polystyrene alloy fiber composite sheet without acrylic acid modification are relatively low, indicating that the compatibility between the vinyl-modified polyphenylene ether and polystyrene is improved, reducing the occurrence of phase separation. Good compatibility makes the interface of the composite sheet more uniform, the stress distribution more uniform, reduces the occurrence of stress concentration points, and helps to improve the mechanical properties of the fiber composite sheet, so that it can withstand stress more stably when subjected to external forces, and improves the modulus and tensile strength.
[0111] From the results of Examples 1, 2, and 3, it can be seen that with the increase in the proportion of vinyl-modified polyphenylene ether in the polyphenylene ether / polystyrene alloy, the tensile strength, interlaminar shear strength, and impact strength of the fiber composite board gradually increase, indicating that with the increase in the proportion of vinyl-modified polyphenylene ether, the overall molecular structure and segment movement of the polyphenylene ether / polystyrene alloy are changed, the degree of entanglement of the molecular chains is increased, and the movement of the molecular chains is restricted, making the material less likely to deform when subjected to stress, which is manifested macroscopically as an increase in the modulus of the fiber composite board.
[0112] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A vinyl-modified polyphenylene ether / polystyrene alloy resin, characterized in that: The invention comprises the following raw materials in parts by weight: 30-70 parts by weight of polyphenylene ether, 30-70 parts by weight of styrene, 1-3 parts by weight of acrylic monomer, 0.5-1 parts by weight of catalyst, 0.5-2 parts by weight of initiator, 1-3 parts by weight of silane coupling agent, 3-16 parts by weight of flame retardant, 0.2-0.6 parts by weight of antioxidant, 0.3-1 parts by weight of heat stabilizer, 0.2-0.4 parts by weight of light stabilizer and 0.05-0.1 parts by weight of ultraviolet light absorber.
2. The vinyl-modified polyphenylene ether / polystyrene alloy resin according to claim 1, characterized in that: The hydroxyl value of the polyphenylene ether is 50 to 1000 g / mol.
3. The vinyl-modified polyphenylene ether / polystyrene alloy resin according to claim 1, characterized in that: The following raw materials are included in parts by weight: 70 parts by weight of polyphenylene ether, 30 parts by weight of styrene, 3 parts by weight of acrylic monomer, 1 part by weight of catalyst, 2 parts by weight of initiator, 3 parts by weight of silane coupling agent, 7 parts by weight of flame retardant, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light absorber.
4. The vinyl-modified polyphenylene ether / polystyrene alloy resin according to claim 1, characterized in that: The acrylic monomer is acrylic acid or methacrylic acid; and / or the catalyst is p-toluenesulfonic acid; and / or the initiator is benzoyl peroxide; and / or the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and / or the flame retardant is selected from one or more of tetraphenyl (bisphenol-A) diphosphate, tetraphenyl resorcinol diphosphate, aluminum hypophosphite, sodium hypophosphite, and melamine cyanurate; and / or the antioxidant is one or more of tris(nonylphenyl)phosphite, distearylthiopropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl alcohol ester, and 2,2-methylenebis(4-methyl-6-tert-butylphenol); and / or the heat stabilizer is one or more of triphenyl phosphite, tris(2,6-dimethylphenyl) phosphite, and trimethyl phosphate; and / or the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole; And / or the ultraviolet light absorber is one or more of titanium oxide, cerium oxide and zinc oxide.
5. The method for preparing the vinyl-modified polyphenylene ether / polystyrene alloy resin according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving polyphenylene ether and acrylic monomer in a solvent and mixing them evenly, passing nitrogen gas for protection, slowly dropping a catalyst, heating and stirring in an oil bath to carry out an esterification reaction, the reaction temperature is 60 to 120° C., the reaction time is 2 to 10 hours, and after the reaction is completed, cooling, filtering, and removing the solvent to obtain a vinyl-modified polyphenylene ether; (2) The vinyl-modified polyphenylene ether obtained in step (1) is mixed evenly with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer, and an ultraviolet light absorber in a mixing device to obtain a premix, and a free radical in-situ polymerization reaction is carried out in a flat vulcanizer at a reaction temperature of 130 to 160° C. for a reaction time of 1 to 5 h. After the reaction is completed, the premix is cooled to room temperature, vacuum dried, and crushed to obtain a premix.
6. A high-strength and high-tenacity glass fiber reinforced composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 30 to 70 parts by weight of glass fiber cloth, 30 to 70 parts by weight of the vinyl modified polyphenylene ether as claimed in claim 5, 30 to 70 parts by weight of styrene, 0.5 to 2 parts by weight of initiator, 3 to 16 parts by weight of flame retardant, 1 to 3 parts by weight of silane coupling agent, 0.2 to 0.6 parts by weight of antioxidant, 0.3 to 1 parts by weight of heat stabilizer, 0.2 to 0.4 parts by weight of light stabilizer and 0.05 to 0.1 parts by weight of ultraviolet light absorber.
7. The high-strength and high-tenacity glass fiber reinforced composite material according to claim 6, characterized in that: The following raw materials are included in proportion by weight: 55 parts by weight of glass fiber cloth, 37 parts by weight of vinyl modified polyphenylene ether, 16 parts by weight of styrene, 2 parts by weight of initiator, 7 parts by weight of flame retardant, 3 parts by weight of silane coupling agent, 0.5 parts by weight of antioxidant, 0.7 parts by weight of heat stabilizer, 0.3 parts by weight of light stabilizer, and 0.2 parts by weight of ultraviolet light absorber.
8. The high-strength and high-tenacity glass fiber reinforced composite material according to claim 6, characterized in that: The density of the glass fiber cloth is 500-600 g / m 2 ; and / or the thickness of the high-strength and high-tenacity fiber-reinforced composite plate is 1.0 to 5.0 mm.
9. The high-strength and high-tenacity glass fiber reinforced composite material according to claim 6, characterized in that: The flame retardant is selected from one or more of tetraphenyl (bisphenol-A) diphosphate, tetraphenyl resorcinol diphosphate, aluminum hypophosphite, sodium hypophosphite, and melamine cyanurate; and / or the antioxidant is one or more of tris(nonylphenyl)phosphite, distearylthiopropionate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, 3,5-di-tert-butyl-hydroxyphenylpropionate octadecyl alcohol ester, and 2,2-methylenebis(4-methyl-6-tert-butylphenol); and / or the heat stabilizer is one or more of triphenyl phosphite, tris(2,6-dimethylphenyl) phosphite, and trimethyl phosphate; and / or the light stabilizer is 2-(2-hydroxy-5-methylphenyl)benzotriazole; And / or the ultraviolet light absorber is one or more of titanium oxide, cerium oxide and zinc oxide.
10. The method for preparing the high-strength and high-tenacity glass fiber reinforced composite material according to any one of claims 7 to 9, characterized in that: The following steps are involved: (i) the vinyl-modified polyphenylene ether is uniformly mixed with styrene, an initiator, a silane coupling agent, a flame retardant, an antioxidant, a heat stabilizer, a light stabilizer, and an ultraviolet light absorber in a mixing device according to a certain proportion to obtain a premix; (ii) applying a release agent on the mold, alternately stacking the glass fiber cloth and the premix, hot pressing at 180-220° C. for 20-40 min under a pressure of 20 MPa, cooling and demoulding, and performing post-treatment to obtain a high-strength and high-toughness glass fiber reinforced composite material.